Knee joint stability following fixation of tibial plateau fracture by angular locking plate fixation - Bari, Jahidul; ., Wang; ., Wu (International Journal of Research in Orthopaedics, 2021)
Background: Injuries to the tibial plateau generally occur because of a force directed either medially or laterally an axial compressive force or both an axial force and force from the side. Tibial plateau fractures resulting frequently in functional impairment. Methods: The total of cases included in the study was 47 in number. More than 20 years old patients of both sexes with tibial plateau fractures attended in the study. Proper informed consent was taken from the patients under the study and purpose of the study was explained. Ethical approval was obtained from the Institutional Ethics Committee. All data were processed, analyzed, and disseminated by MS Office and Statistical package for social sciences (SPSS) version 26 as per need. Results: In this study, for majority (51%) patients <12 weeks were in needed for union. Besides these, for 23.40% and 21.28% patients, time for union were 12-14 and >14 weeks respectively. Unfortunately, in 4.26%% cases (n=2) incidence of non-union was occur. The mean period of radiological union was 12.75 weeks (12-16 weeks). Most of the patients were allowed complete weight bearing at 11 to 14 weeks. Average time gap for complete weight bearing was 13.5 weeks. In assessing the knee stability of the participants, we observed, the mean (±SD) angle of knee joints was 112.08 ±12.32 degree. The mean (±SD) Knee Society Score (KSS) was found 77.51 ± 8.16. As per the functional outcomes among all the participants, majority of them (57.45%) got ‘good’ results whereas 29.79% got ‘Excellent’ and 8.51% got ‘Poor’ results. Conclusions: Satisfactory knee joint stability for patients with tibial plateau fracture angular locking plate fixation technic may be considered as an effective treatment method for orthopedic surgeons.